The cybersecurity workforce of tomorrow - Nizich, Michael (Future of work (Emerald Publishing), 2023)
The field of cybersecurity - the protection of electronic data - offers one of the fastest growing job markets today. As the sector grows in importance there will be a rapidly growing demand for qualified analysts, cryptographers, engineers, architects, managers, and executive leaders. The Cybersecurity Workforce of Tomorrow discusses the current requirements of the cybersecurity worker and analyses the ways in which these roles may change in the future as attacks from hackers, criminals and enemy states become increasingly sophisticated. The author's predictions are based on the inevitable changes that will come for the cybersecurity industry including: More rigid federal, state, and global security requirements and accountability The increasing complexity and quality of cyber-attacks and the skillsets of the attackers The expansion and acceptance of the dark web as a marketplace for stolen data The increasing use of cyber-attacks in political and economic confrontations between nation states Experienced practitioner and academic Michael Nizich examines the current and future human resources requirements of the cybersecurity market. His focus on workforce preparation, education and emerging technologies is essential reading for executives and cybersecurity professionals alike.